TOWARDS A KNOWLEDGE CULTURE: MANAGING THE INFORMATION ADVANTAGE WITH REFERENCES TO MALAYSIA - Agha, Syed Salim; Agha, Syed Salim (Malaysian Journal of Library and Information Science, 2017)
Agha, S. S. (1996). Towards a Knowledge Culture: Managing the Information Advantage with References to Malaysia. Malaysian Journal of Library & Information Science, Vol.1, no. 2: 51-62 Provides a run up of the developments relating to education, culture, libraries, books, information and information technology. The pervasiveness and importance of information is elaborated upon. The development of information as it goes through its various phases of utility is explained. The strategic integration of information and various emerging technologies are looked upon as an evolutionary development. Analyses the current situation identifying key issues, which when summed up are referred to as the â€œinformation advantageâ€. It is emphasised that while technology plays a strategic role what is often ignored is the information content and its effective and integrated management with key issues. The failure to manage this information advantage would result in a great opportunity loss. Managing the information advantage has its objective in the eventual development of a knowledge culture in a society. Knowledge culture is elaborated upon at the levels of the individual, the organization, the nation and the world.